Myelodysplastic syndromes: a review of therapeutic progress over the past 10 years. Issue 6 (2nd June 2020) - Feld, Jonathan; Belasen, Abigail; Navada, Shyamala C
ABSTRACT: Introduction: Myelodysplastic syndromes (MDS) represent a range of bone marrow disorders, with patients affected by cytopenias and risk of progression to AML. There are limited therapeutic options available for patients, including hypomethylating agents (azacitidine/decitabine), growth factor support, lenalidomide, and allogeneic stem cell transplant. Areas covered: This review provides an overview of the progress made over the past decade for emerging therapies for lower- and higher-risk MDS (MDS-HR). We also cover advances in prognostication, supportive care, and use of allogeneic SCT in MDS. Expert opinion: While there have been no FDA-approved therapies for MDS in the past decade, we anticipate the approval of luspatercept based on results from the MEDALIST trial for patients with lower-risk MDS (MDS-LR) and ringed sideroblasts who have failed or are ineligible for erythropoiesis stimulating agents (ESAs). With growing knowledge of the biologic and molecular mechanisms underlying MDS, it is anticipated that new therapies will be approved in the coming years.